Photographs of the Soviet Settlements on Svalbard - Haugdal, Elin Kristine (Nordlit, 2020)
Photographic recordings from the 1950s–1970s give us glimpses into the Soviet settlements on Svalbard during the Cold War period. The majority of these pictures have been taken by Norwegians during friendly exchanges with the inhabitants in Barentsburg and Pyramiden, and demonstrate how important culture and sport were as a contact zone. These pictures also testify that the Soviets invested more seriously in their welfare, culture, education and family life on Svalbard than the Norwegians did. Photography seems to be a way of seeing, meeting and understanding others, and a way of confirming the existence of a common world on Svalbard. However, the Soviet Consul’s strict control of photographing practices may be seen as part of a propagandizing regime, in line with the Soviet imagery which spread even to this remote Arctic place. Owing to the cultural museums’ digitizing projects and to private sharing on social media, photographs from this period have become increasingly available, but without rules or guiding principles as to how to put them together and interpret them. Thus, to the contemporary viewer these images offer the possibility to make visual montages, and to reveal the singular image’s meanings well beyond both the Soviet authorities’ and the photographer's control. This article, while making such a montage, discusses how photography might shape and change our historical understanding of people and places.